Management of food waste containing animal protein in the process of liming and aerobic composting - Głowacka, Anna; Bering, Sławomira; Tarnowski, Krzysztof; Mazur, Jacek (Instal, 2024)
Food waste containing animal protein (FW-AP) processing was carried out it two stages: hygienization in the liming process and aerobic composting in real conditions. Pilot compost prisms consisted of 1-1,2 tons of wastes mix contained: (i) sewage sludge, dried to 14,5% of dry weight, (ii) food waste containing animal protein (FW-AP), fragmented to size 12mm, hygienized with calcium oxide CaO; dry matter content, after liming, was equal to 18%; (iii) bulking agents: straw and biowaste such as leaves, grass, waste paper, 66-75% dry weight; (iv) inoculate, 40% of dry weight. In the heaps, the content of limed FW-AP was 20%, 30% and 40%. After about 2 months of composting, the finished compost was obtained. The final product was characterized by the following parameters: moisture 40-52%, pH 7,0-7,4, organic matter 59,4-62,3%, Total Kjeldahl Nitrogen 26,6 – 69,5 g N/kg dry matter by weight., Total phosphorus 17,6 – 63,0 g P/kg d. m. Presented method is a simple and effective way to convert waste into a product. The contribution of food waste containing animal protein in total compost prism mass on a level up to 40% allows for the rapid processing of large amounts of waste. Final composts meet the requirements given for soil improvers or mineral – organic fertilizers.